Thematic analysis of lived experiences of gay survivors of childhood sexual abuse - Kishimoto, Ken Terrado; Vinluan, Lorelei R.; Gomez, Marie Grace Avelino; Salubayba, Teodora M. (Quezon City College of Education, University of the Philippines Diliman, 2017)
This study sought to describe and understand the lived experiences, coping mechanisms and impact of childhood sexual abuse (CSA) in the present-life of survivors as experienced by some Filipino gays. Qualitative-phenomenological research design was employed to explore and gather a rich description of the phenomenon being studied. Six participants were purposively selected. Participants went through recorded, personal one-on one interview series. Six emergent themes were identified to describe the lived experiences of gay survivors. These are the “living in discrete while growing up”, “self-blaming”, “sexualization” and “re-victimization”, “stolen childhood” as perceived by the participants and the “psychological and physical trauma” they endured. Impacts in their current life are the issue in establishing trust to other people, deviated gender preference, imprinted arousal and aggressive sexual pattern and the shattered self-image perception. Coping mechanisms evident to these survivors are “acceptance” and “resilience”, “avoidance”, “denial”, “suppression” and “sublimation”. Coping mechanisms varies on how the survivors view their sexual abuse experience, and impacts of CSA vary from asymptomatic to lifelong disabling psychological and behavioral consequences. Identifying risk factors, population with reported cases of childhood sexual abuse, straight male survivors, and unsuccessful individuals with childhood sexual abuse experience are some of the recommendations to further the study. Programs to recommend based from the results were psychoeducation for family, community, school and survivor/s themselves, psycho-therapies and the online and personal support groups.
Thesis (Master of Arts in Education - Guidance)--University of the Philippines, Diliman
Includes bibliographical references (pages 99-108).
Keywords: Child sexual abuse; Sexually abused children; Adult child sexual abuse victims; Sexual abuse victims